Utilization of non-pneumatic anti-shock garment and associated factors for postpartum hemorrhage management among health care professionals' in public hospitals of Jimma zone, south-West Ethiopia, 2019 - Gadisa Bekele; Gemechu Terefe; Makeda Sinaga; Sena Belina (BMC, 2020)
Abstract Background Non- pneumatic anti-shock garment is a unique, life -saving first -aid device made of neoprene and velcro, which is used for treatment of women with postpartum hemorrhage. Maternal mortality in the world still very high and postpartum hemorrhage is the leading cause of maternal mortality worldwide. Objective This study was aimed to assess the utilization of non-pneumatic anti-shock garment and associated factors for postpartum hemorrhage management. Methods Facility based cross-sectional studies design both quantitative and qualitative data collection methods were employed among 210 health care professionals and 10 key informants respectively. Bivariable and multivariable logistic regression was done to identify factors associated with non-pneumatic anti-shock garment utilization. Qualitative data was transcribed, translated and triangulated with quantitative findings. Results Seventy six (36.2%) of the respondents used non-pneumatic anti-shock garment in their hospitals for management of post-partum hemorrhage. Having good knowledge [(AOR = 3.96, 95% CI: (1.67, 9.407)], having positive attitude [(AOR = 3.54, 95% CI: (1.37, 9.13)], attending training [AOR = 13.156, 95% CI: (4.81, 36.00], having two and above non-pneumatic anti-shock garment at their hospitals [AOR = 8.7, 95% CI: (2.89, 26.20)] were significantly associated with utilization of non-pneumatic anti-shock garment. ... "I didn't use non-pneumatic anti-shock garment for the management of postpartum hemorrhage complication before because I have no training and experience how to use it." Conclusion The utilization of non-pneumatic anti-shock garment for the management of postpartum hemorrhage was low. Having positive attitude, having good knowledge and training on non-pneumatic anti-shock garment were statically associated with its use. The health care professionals that involved in the maternity service should be trained on how to use this important garment in the management of postpartum hemorrhage.